Analysis of Improving the Quality of Outpatinent Service At Hospital X Through Triz Method (Theory of Inventive Problem Solving) - Silvia Dewi; Antono Surjoputro; Suhartono Suhartono (Jurnal Indonesia Sosial Teknologi, 2024)
The aim of the research in this introduction is to analyze and improve the quality of outpatient services at Hospital X using the TRIZ (Theory of Inventive Problem Solving) method. This research seeks to find innovative solutions to improve the quality of hospital services using creative principles from TRIZ, which is expected to increase patient satisfaction and strengthen the hospital's credibility in the eyes of the public. This research also seeks to utilize the SERVQUAL model to identify gaps between customer expectations and perceptions of service quality, so that it can produce systematic and sustainable improvements in health services. Method of collecting data are primary data and secondary data. The gaps identified from the expectation and perception questionnaire in the hospital outpatient service include doctors not arriving as scheduled and waiting times in the outpatient pharmacy exceeding 60 minutes. Utilizing TRIZ inventive principles, such as 35 (Parameter Changes), 30 (Flexibility), 34 (Discarding and Recovering), and 2 (Taking Out), can enhance the timeliness of hospital outpatient services. By applying TRIZ inventive principles 10 (Preliminary Action), 19 (Periodic Action), 23 (Feedback), and 28 (Mechanics Substitution), the hospital can expedite outpatient pharmacy services. Implementing preliminary preparation, periodic action, feedback mechanisms, and technology will help reduce patient waiting times, improve efficiency, and ensure better service. These recommendations will be adjusted according to the actual conditions in the hospital. Future research can further investigate Lean management in outpatient pharmacy to identify and eliminate waste.